“Marketing strategies for the launch of the new rock music productions to attract youth in Turkey” - Özkarslı, Soner (My University, 2008)
TEZ OZETI Rock Muzik, 90’ lardan bugune kadar buyuk ilerleme kaydederek Turkiye’ deki altin cagini yasiyor. Yeni tarzlar, yeni olusumlar, sound ve imajlar onceki donemlere nazaran cok daha etkileyici ve basarili olmaklar beraber, Turk muzik dinleyicisi de Rock muzige ilgi, alaka ve bagliligini arttirmis, Rock muzik kimligini fazlasiyla benimsemeye baslamistir. Ekonomik sartlar ve dinleyicinin tuketim davranislari, korsan ve Internet’ in de etkisiyle, album satislarini dusurmus, muzik endustrisinin seklinin biraz daha degismesine neden olmaya baslamistir. Dinleyici, album almaktan cok Internet’ten indirmeyi veya korsan album almayi tercih etmis, bunun sonucunda da plak sirketleri muzisyenler ile yaptiklari kontratlarin seklini degistirmis ve organizayon boyutundan kazanilan gelirleri arttirici calismalara agirlik verilmeye baslanmistir. Bu calisma, Turk Rock muzik dinleyicisin kimligi, duygu ve dusunceleri, beklentileri ve gozlemlerini ele alarak, ‘tuketici davranislari’ ni analiz etmektedir. Turk Rock muziginin onde gelen eksperlerinin; dinleyici profili, korsan ve internet, muzikte medyanin rolu, sound&imajlar, reklam&promosyonlar gibi muzigin pazarlanmasinda etkili olan konular uzerindeki fikir ve gozlemleri, yeni cikan rock muzik produksiyonlarini etkili pazarlama stratejilerinin gelistirilmesini amaclayan bu calismada onemli rol oynamistir. Turk rock muzik dinleyicisinin zayif tuketim aliskanlari nedeniyle, album almak yerine konser ve organizasyonlara karsi ilgisinin artmasi, ‘Win-win’ anlasmalarinin yapilmasina ve artik plak sirketlerinin, organizasyon ve menajerlik gorevlerini de iclerine alarak, bir butun seklinde ‘360 derece’ adi verilen bir kurumsal yapiya donusmeye baslamasina neden olmustur. Turkiye’de Rock muzik bu yonde ilerlemeye baslamis, albumun satis ve dinleyicinin satin alma kaygisinin olmamasi dolayisiyla, yeni tarzlara, olusumlara, imajlara yonelik ilgi ve begeni artmis, organizasyonlar da bu ilgi ve baglilik sayesinde kazanclari arttirmaya baslamistir. Son 10 yilda, Turkiye’de hizli tuketilen rock muzik, Anadolu ve yabanci muzik tarzlarinin harmanlanmasi, farkli ve yabanci soundlarin yakalanmasi ile daha da gelismis, ‘globallesme’ ve ‘glokallesme’ muzikte de kendini gostermeye baslamistir.

OF THESIS STUDY Rock music have been improving since 90’s in Turkey and living its golden age today. New styles, new formations, sounds and images are so effective and successful when it is compared with the old term rock music in Turkey and Turkish audience have increased their interest and involvement towards rock music by adopting themselves to rock music identity. Economic conditions and consumer behaviours of the audiences, also with the effects of Internet and piracy, caused the decrease in album sales and change in the structure of the music industry. Audiences prefer to download songs or buy pirated copies instead of purchasing original albums and as a result, label records have changed the rules and conditions of the contracts that focus on the revenues of the organizations, live events of the bands. This study analyze ‘consumer behaviors’ of the audiences by dealing with the identity, emotions and ideas, expectations and observations of the Turkish rock music audience. Moreover, opinions of the Turkish rock music experts about the music marketing tools such as audience profiles, piracy & Internet, media acts, sounds & images, advertisements & promotions played a crucial role in the thesis study that aims to improve efficient marketing strategies for the new launched rock music productions in Turkey. Weak consumption habits lead the audience to prefer to attend concerts and live events instead of buying original rock music albums and interest towards organizations caused ‘win-win’ contracts and encouraged label records to take the responsibilities and missions of organizational-managerial acts in the name of ‘360 degree’ formations. Today, lack of anxiety of musicians for selling album and lack of desire of audiences to purchase albums caused the existence and interest for new styles, new formations and images. Organizations increased their revenues related with the increasing trend of rock music in Turkey. Rock music that is consumed up so fast in Turkey has been improved in the last decade by the harmonization of Anatolian and foreign sounds, also by creation of new sounds & images that are similar with successful foreign bands, and it is important that ‘globalisation’ – ‘glocalisation’ show their effect on marketing of music productions as they are so effective for all marketing acts and strategies.
Keywords: Pazarlama; Pazarlama Stratejileri; Üretim Yönetimi